Microencapsulation of β-Carotene by Spray Drying: Effect of Wall Material Concentration and Drying Inlet Temperature - Luiz C. Corrêa-Filho; Maria M. Lourenço; Margarida Moldão-Martins; Vítor D. Alves (International Journal of Food Science)
Carotenoids are a class of natural pigments found mainly in fruits and vegetables. Among them, β-carotene is regarded the most potent precursor of vitamin A. However, it is susceptible to oxidation upon exposure to oxygen, light, and heat, which can result in loss of colour, antioxidant activity, and vitamin activity. Thus, the objective of this work was to study the microencapsulation process of β-carotene by spray drying, using arabic gum as wall material, to protect it against adverse environmental conditions. This was carried out using the response surface methodology coupled to a central composite rotatable design, evaluating simultaneously the effect of drying air inlet temperature (110-200°C) and the wall material concentration (5-35%) on the drying yield, encapsulation efficiency, loading capacity, and antioxidant activity. In addition, morphology and particles size distribution were evaluated. Scanning electron microscopy images have shown that the particles were microcapsules with a smooth surface when produced at the higher drying temperatures tested, most of them having a diameter lower than 10 μm. The conditions that enabled obtaining simultaneously arabic gum microparticles with higher β-carotene content, higher encapsulation efficiency, and higher drying yield were a wall material concentration of 11.9% and a drying inlet temperature of 173°C. The systematic approach used for the study of β-carotene microencapsulation process by spray drying using arabic gum may be easily applied for other core and wall materials.